Polyadenylic acid sequences in the RNA of Hyphomicrobium. - Schultz, G A (1978)
Heterogeneous RNA containing polyadenylic acid [poly(A)] sequence has been isolated from Hyphomicrobium by affinity chromatography on oligothymidylic acid cellulose and polyuridylic acid Sepharose columns. About 0.1 to 0.3% of [3H]adenine-labeled RNA over a 60-min period is associated with poly(A) sequences. This percentage decreases to about 0.03 in a 20-h labeling period. The poly(A) tracts recovered after digestion with ribonuclease A and T1 are composed of greater than 95% adenine residues and are up to 200 nucleotides in length with a predominant range of 15 to 40 nucleotides. Adenosine and AMP are present in the ratio of 1:36 in alkaline digests of Hyphomicrobium poly(A) tracts. This is compatible with nucleotide lengths determined on acrylamide gels and location at the 3'-OH terminus of the RNA molecule.